Brief Report: Young Age and Sex Work Are Associated With HIV Seroconversion Among Transgender Women in São Paulo, Brazil. (1st September 2021) - Amelia de Sousa Mascena Veras, Maria; Roza Saggese, Gustavo S.; Gomez Junior, José L.; Silveira, Paula; Paiatto, Beatriz; Ferreira, Denis; Alves de Souza, Paola; Calado, Rodrigo; Castejon, Márcia Jorge; Yamashiro, Rosemeire; Fernando de Macedo Brígido, Luis; Turner, Caitlin; et al.
Abstract : Background: Transgender women worldwide have the highest prevalence of HIV and the lowest access to prevention among groups at risk of HIV. However, few longitudinal studies have directly measured HIV incidence and identified predictors of HIV acquisition among transgender women. Setting: Sa[Combining Tilde]o Paulo, Latin America's largest city. Methods: We conducted a longitudinal study among transgender women in Sa[Combining Tilde]o Paulo. Participants were recruited by a long-chain peer referral process from May 2017 to July 2019. Those aged 18 years and older and who were HIV-negative at baseline were retested every 6 months up to 18 months. HIV incidence was calculated by dividing the number of seroconversions by the person-years (PYs) of follow-up; 95% confidence intervals (CIs) were constructed assuming a Poisson distribution. Conditional maximum likelihood ratios assessed differences in HIV incidence by risk factors. Results: A racially/ethnically diverse sample of 545 HIV-negative transgender women was enrolled. In 485.5 PYs of follow-up, 13 seroconversions were observed, yielding an incidence of 2.68 per 100 PYs (95% CI: 1.43 to 4.58). HIV incidence was significantly higher among transgender women aged 18–24 years (rate ratio 3.85, 95% CI: 1.24 to 12.93) and among those who engaged in sex work in the preceding month (rate ratio 5.90, 95% CI: 1.71 to 26.62). Conclusions: HIV transmission continues at a high rate among transgender women in Brazil. Factors such as young age, lower level of education, and limited employment opportunities may lead to dependence on sex work that in turn increases HIV risk. Transgender-friendly prevention services, particularly programs delivering pre-exposure prophylaxis, are urgently needed.